Antropologi Kristianitas: Tinjauan Tantangan, Batas-batas, dan Peluang Kajian Perubahan Keagamaan dalam Disiplin Antropologi - Ardhianto, Imam; Claudia, Lingkan (Jurnal Masyarakat dan Budaya, 2023)
This study critically reviews anthropological literature of the Anthropology of Christianity sub-field, focusing on the Pentecostal, evangelical, and charismatic (P/I/C) traditions. It departs from the theoretical debates on cultural change, which plays an important contribution to the broader debates in the discipline of social and cultural transformation. In investigating the debates, this article uses literature research methodologies to chart the paradigmatic and conceptual transformation of studying religious change. This study argues that the anthropology of Christianity sub-field has been contributing significant perspective to understand cultural change, starting from adding a new conceptual explanation that cannot be covered by the perspective that is only obsessed with continuity, assimilation, and cultural transformation. It proposes a perspective that emphasizes cultural discontinuity and the relevance of the reality of the socio-religious organization. The article concludes that the shift occurred as much evidence on social-religious change revealed the increasing emergence of denominations that took the importance of a total disconnection to pre-Christian tradition and culture and a strong push for egalitarian religious authority as central to religious doctrine. This perspective can contribute to studies of religious change in Indonesia and Southeast Asia.